2010
DOI: 10.2139/ssrn.1692645
|View full text |Cite
|
Sign up to set email alerts
|

Size, Value and Liquidity: Do They Really Matter on an Emerging Stock Market?

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 55 publications
3
29
0
2
Order By: Relevance
“…Rouwenhorst () finds value and size effects for emerging markets for a period from 1982 to 1987, but does not find the role of liquidity. Similarly, Lischewski and Voronkova () find the size and value effects but not liquidity effect for the Polish market in Central and Eastern Europe. Barry, Goldreyer, Lockwood, and Rodriguez () study the size and value effects in 35 emerging markets over the period 1985–2000, and find the existence of value effect but not the size effect measured by absolute firm size.…”
Section: Introductionmentioning
confidence: 84%
“…Rouwenhorst () finds value and size effects for emerging markets for a period from 1982 to 1987, but does not find the role of liquidity. Similarly, Lischewski and Voronkova () find the size and value effects but not liquidity effect for the Polish market in Central and Eastern Europe. Barry, Goldreyer, Lockwood, and Rodriguez () study the size and value effects in 35 emerging markets over the period 1985–2000, and find the existence of value effect but not the size effect measured by absolute firm size.…”
Section: Introductionmentioning
confidence: 84%
“…Later on, Barry et al (2002), Kargin (2002), Rouwenhorst and Salomons (2003) have demonstrated benefits of stock selection based on value-related variables measures, like price-to-book ratio, price-to-earnings ratio or price-to-cash flow ratio for EEM investors. Also, the most recent studies confirm that the value premium is present in emerging markets, although it may vary from country to country (e.g., Dimson et al, 2014;Cakici et al, 2013;Lischewski and Voronkova, 2010;Hanauer and Linhart, 2015;Zaremba, 2015). Most recently, Zaremba and Czapkiewicz (2016) identified and replicated ten various value-oriented return-predictive signals in a very similar sample covering the Czech Republic, Hungary, Poland, Russia, and Turkey.…”
Section: Related Literaturementioning
confidence: 92%
“…In recent studies researchers have found relation between stock returns and trading volume (Chen, Firth and Rui, 2001;Khan and Rizwan, 2001;Lee and Rui, 2002;Pisedtasalasai and Gunasekarage, 2008). Furthermore Lischewski (2012) finds that portfolios with high trading volume tends to be followed by high returns and vice versa. Khaled & Titi (2013) reveals that trading volume responds positively to stock return.…”
Section: Literature Reviewmentioning
confidence: 99%